2015
DOI: 10.1590/0103-8478cr20130307
|View full text |Cite
|
Sign up to set email alerts
|

Relative humidity during cold storage on Postharvest quality of 'Niagara Rosada' table grapes

Abstract: This study aimed to evaluate the effect of different levels of relative humidity (RH) on the maintenance of Postharvest quality of 'Niagara Rosada'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…For example, prior work has found that relative humidity values between 90% and 95% offers the best conditions to maintain the postharvest quality of 'Niagara Rosada' table grapes [43]. However, higher relative humidity is also highly favorable to the development of pathogens that promote berry decay.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prior work has found that relative humidity values between 90% and 95% offers the best conditions to maintain the postharvest quality of 'Niagara Rosada' table grapes [43]. However, higher relative humidity is also highly favorable to the development of pathogens that promote berry decay.…”
Section: Discussionmentioning
confidence: 99%
“…According to Pereira et al (2018), the weight of grapes constantly decreases over time; however, this loss occurs more slowly depending on the RH conditions. Pinto et al (2015) stated that the ideal humidity range for table grapes was between 90% and 95% for greater maintenance of product quality.…”
Section: Resultsmentioning
confidence: 99%
“…Gray mold can develop in the vineyard and spread rapidly among berries at harvest, and in the period postharvest under cold storage, during long distant transport, and also during the shelf life period (Romanazzi et al, 2012). Sometimes, decay incidence is not observed when bunches are kept under cold storage, but during shelf life, it can reach around 10-20% incidence, as this is the case for 'Niágara Rosada' grapes kept 21 days under cold storage plus two days at room temperature (Pinto et al, 2015). The onset of these symptoms can occur due to the reduced synthesis of phenolic compounds (for instance, anthocyanins), and to epidermal softening (Pezet et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…However, the market supply of table grapes for larger periods relies on postharvest strategies, such as cold storage, which can extend the maintenance of postharvest quality of the bunches. The storage temperatures and periods depend on the cultivar used, but most commonly they are around 0°C, with storage periods from 20 to 120 days (Brackmann et al, 2000;Sen & Kesgin, 2014;Youssef & Roberto, 2014b;Pinto et al, 2015;Youssef et al, 2015).…”
Section: Introductionmentioning
confidence: 99%